Neurochemical monitoring of fatal middle cerebral artery infarction - Berger, Christian; Annecke, Andrea; Aschoff, Alfred; Spranger, Matthias; Schwab, Stefan (Stroke, 1999)
Background—Microdialysis is a method for neurochemical monitoring that has been applied more frequently over the past few years in patients suffering from subarachnoid hemorrhage, acute brain injury, and stroke. It is used to study the course of extracellular molecules of low molecular weight, such as excitatory amino acids or metabolic end products.Case Description—We report the case of a 43-year-old patient suffering from left hemispheric stroke with a space-occupying postischemic edema leading to a considerable mass effect on the contralateral side. For treatment of severe edema, hypothermia was initiated. The microdialysis and intracranial pressure probe were placed into the noninfarcted hemisphere. A massive increase in levels of glutamate, glycerine, and the lactate-pyruvate ratio was measured 24 hours before intracranial pressure elevation was observed and brain death occurred.Conclusions—Monitoring excitatory amino acids, glycerine as a membrane component, and lactate-pyruvate ratio as an energy marker by microdialysis is a useful tool to increase our understanding of biochemical events in secondary brain damage. For future prevention of secondary ischemia in patients with massive stroke, close neurochemical monitoring might be valuable to improve therapy, particularly in the critically ill.